Desarrollo de una aplicación web y móvil mapa parlante en el Centro de Salud Chambo - Lucio Barragan, Noralma Alexandra (2024)
This research project embarked on a groundbreaking journey, focusing on the development of an innovative application with web and mobile access to the Mapa Parlante at the Centro de Salud Chambo. This application revolutionizes the management of risk factors, vulnerable groups, priority groups, and biological, socioeconomic, and environmental health risks through the geospatial visualization of data obtained from the Familiar Register. The agile SCRUM methodology, a testament to our commitment to efficiency and adaptability, guided the software development process. Every step was carefully planned, with a client-server architecture with microservices chosen to ensure optimal performance. Strategically selected methodologies and tools were used in the construction of the application: PostgreSQL as the database management system, Nest.js in the backend, and Angular together with Tailwind CSS for the frontend development. Geo server and Open Layers enriched the geospatial data management and map interactivity, while Bing Maps and Open route service provided access to detailed maps and routing services. The usability evaluation, based on the ISO/IEC 25010 model using a quantitative approach, highlighted high scores in learnability (92.56 points), operability (93.54 points), user error protection (93.54 points), and interface aesthetics (94.00 points). Combined with the selected technology, this agile approach culminated in a functional, dynamic, and highly interactive application.